HUBUNGAN ANTARA PENGUASAAN UNSUR INTRINSIK DAN KETERAMPILAN MENULIS CERPEN: STUDI KORELASIONAL PADA SISWA KELAS X SMA - Ratu Parosa, Jovita; Setiawan, Budhi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low short story writing skills of tenth-grade students at SMA Negeri 1 Kartasura, caused by difficulties in designing coherent plots and developing characters. The aim of this study is to describe the relationship between the mastery of intrinsic elements and short story writing skills. This study employed a quantitative correlational method with a sample of 72 students selected through cluster random sampling. Data collection techniques included an objective test to measure the mastery of intrinsic elements and a product test to measure short story writing skills. The research instruments underwent validity and reliability testing, yielding a KR-20 coefficient of 0.939 for variable X and a ratings reliability of 0.97 for variable Y. The results showed a positive and significant correlation between the mastery of intrinsic elements and short story writing skills, with a correlation coefficient () of 0.624 and a significance of . The mastery of intrinsic elements contributes 38.9% to the variation in students' short story writing skills. This proves that theoretical understanding of story-building elements serves as an essential foundation for producing high-quality narrative works at the high school level.